Cardioprotective potential of simvastatin in the hyperhomocysteinemic rat heart - Ankur Rohilla; M U Khan; Razia Khanam (Wolters Kluwer Medknow Publications, 2012)
The present study investigated the probable role of simvastatin, 3-hydroxymethyl-glutaryl coenzyme A (HMG-CoA) reductase inhibitor, in abrogated cardioprotection in hyperhomocysteinemic (Hhcy) rat hearts. Isolated Langendorff's perfused normal and Hhcy rat hearts were subjected to 30-min global ischemia (I) followed by 120-min reperfusion (R). Assessment of myocardial damage was done by measuring infarct size and analyzing the release of lactate dehydrogenase (LDH) and creatine kinase (CK-MB) in coronary effluent. In addition, the oxidative stress in the heart was assessed by measuring lipid peroxidation and superoxide anion generation. I/R produced myocardial injury in normal and Hhcy rat hearts by increasing myocardial infarct size, LDH and CK in coronary effluent and oxidative stress. Hhcy rat hearts showed enhanced myocardial injury and high oxidative stress as compared to normal hearts. Treatment with Simvastatin (10 μMol) afforded cardioprotection against I/R-induced myocardial injury in normal and hyperhomocysteinemic rat hearts as assessed in terms of reductions in myocardial infarct size, LDH and CK levels in coronary effluent and oxidative stress. The reductions in the high degree of oxidative stress may be responsible for the observed cardioprotection afforded by simvastatin against I/R-induced myocardial injury in normal and hyperhomocysteinemic rat hearts.